Evaluation of the Sragi Secondary Channel of the Kaliwadas Irrigation Area, Pekalongan Regency - Wanto, Sri; Masvika, Hendra; Cahyono, Dhamang Budi; Purwanti, Hani (Universitas Islam Sultan Agung, 2024)
The Sragi secondary channel is located in the Kaliwadas irrigation area, Pekalongan Regency has a length of 7,587 m. The position of the channel is in a rice field area which is used to optimize irrigation to support agricultural business productivity. The existing condition of the channel in the form of native soil causes frequent leaks. Technical handling is needed to repair irrigation buildings in the form of a study on the existing condition of the Sragi secondary channel through field surveys and checking physical conditions. Furthermore, identification of the level of damage to irrigation channels is carried out. From the problems that arise at the identification stage, recommendations are then given in the form of proposals for improvements to buildings and irrigation channels. The results of the field survey in the form of network tracing provide data that the level of physical and functional damage to the Sragi secondary channel infrastructure reaches >40%. The condition is categorized as very bad with the classification of severely damaged which requires repair or replacement. Most of the damage in the form of spots or localized occurred on the existing lining of masonry and precast concrete starting from Hm 50+00 to Hm75+68. The recommendations for improvement are in the form of dismantling the existing precast concrete lining according to the point of damage. It is recommended to repair the lining using K-300 precast concrete so that the structure of the irrigation channel is safe against the risk of deformation.